Canopy-Forming Macroalgae Facilitate Recolonization of Sub-Arctic Intertidal Fauna and Reduce Temperature Extremes - Ørberg, Sarah B.; Krause-Jensen, Dorte; Mouritsen, Kim N.; Olesen, Birgit; Marbà, Núria; Larsen, Martin H.; Blicher, Martin E.; Sejr, Mikael K. (Frontiers in Marine Science, 2018)
Ice can be an important structuring factor physically removing intertidal flora and fauna. At high latitudes in particular, the removal of canopy-forming algae by ice scour may be important as their canopy may serve to modify the extreme environment for marine organisms at low tide. We simulated the effect of ice scouring by manipulating the biomass of the canopy-forming algae Ascophyllum nodosum in a sub-Arctic fjord [“Full canopy,” “Reduced canopy,” “Bare (start),” “Bare (annual)”]. Over a three-year period, we quantified key physical parameters and the recolonization of flora and fauna to test the hypothesis that A. nodosum and rock rugosity facilitate recolonization of sub-Arctic intertidal fauna and that potential facilitation could rely on an ability of A. nodosum canopy to modify air temperature and ice scour. Finally, we estimated the recovery period of A. nodosum canopy height to pre-disturbance levels based on estimated early growth rates. We found that A. nodosum canopy facilitated higher species richness and recolonization of dominating faunal species (Littorina saxatilis, Littorina obtusata, Mytilus edulis, and Semibalanus balanoides), and also significantly reduced the high temperatures in summer and raised the low temperatures in winter. The abundance of M. edulis and A. nodosum recolonization increased significantly with rock rugosity and the recovery of A. nodosum canopy height was estimated to a minimum of 15 years. We conclude that algal canopy and rock rugosity play key roles in structuring sub-Arctic intertidal communities, likely by modifying environmental stress such as extreme temperature, desiccation, and by increasing the settling surface and the habitat complexity. As the distribution of canopy-forming algae is expected to shift northward, they may act as a key habitat facilitating a northward colonization of intertidal fauna in the Arctic. We highlight the importance of considering scales relevant to biological communities when predicting impacts of climate change on distributional patterns and community structure in the Arctic intertidal.